Household catastrophic health expenditure for COVID-19 during March-August 2021, in South India: a cross-sectional study - Elumalai Rajalakshmi; Akhil Sasidharan; Bhavani Shankara Bagepally; Muthusamy Santhosh Kumar; Ponnaiah Manickam; T. S. Selva Vinayagam; P. Sampath; K Parthipan (BMC, 2023)
Abstract Background The Coronavirus disease 2019 (COVID-19) pandemic increased the utilisation of healthcare services. Such utilization could lead to higher out-of-pocket expenditure (OOPE) and catastrophic health expenditures (CHE). We estimated OOPE and the proportion of households that experienced CHE by conducting a cross-sectional survey of 1200 randomly selected confirmed COVID-19 cases. Methods A cross-sectional survey was conducted by telephonic interviews of 1200 randomly selected COVID-19 patients who tested positive between 1 March and 31 August 2021. We collected household-level information on demographics, income, expenditure, insurance coverage, direct medical and non-medical costs incurred toward COVID-19 management. We estimated the proportion of CHE with a 95% confidence interval. We examined the association of household characteristics; COVID-19 cases, severity, and hospitalisation status with CHE. A multivariable logistic regression analysis was conducted to ascertain the effects of variables of interest on the likelihood that households face CHE due to COVID-19. Results The mean (95%CI) OOPE per household was INR 122,221 (92,744-1,51,698) [US$1,643 (1,247-2,040)]. Among households, 61.7% faced OOPE, and 25.8% experienced CHE due to COVID-19. The odds of facing CHE were high among the households; with a family member over 65 years [OR = 2.89 (2.03-4.12)], with a comorbid individual [OR = 3.38 (2.41-4.75)], in the lowest income quintile [OR = 1.82 (1.12-2.95)], any member visited private hospital [OR = 11.85 (7.68-18.27)]. The odds of having CHE in a household who have received insurance claims [OR = 5.8 (2.81- 11.97)] were high. Households with one and more than one severe COVID-19 increased the risk of CHE by more than two-times and three-times respectively [AOR = 2.67 (1.27-5.58); AOR = 3.18 (1.49-6.81)]. Conclusion COVID-19 severity increases household OOPE and CHE. Strengthening the public healthcare and health insurance with higher health financing is indispensable for financial risk protection of households with severe COVID-19 from CHE.